“Pengaruh Pendapatan, Tax to Book Ratio, Taxable Income, Deferred Tax dan Current Tax Terhadap Kinerja Keuangan Perusahaan pada Perusahaan Layanan Investasi dan Perdagangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021 - patar hutagaol (Fakultas Ekonomi Prodi Akuntansi, 2023)
This study aims to determine the effect of income, tax to book ratio, taxable income, deferred tax and current tax on the performance of investment and trade service companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The method of this study uses a quantitative approach by analyzing secondary data. The population of this study were companies listed on the IDX with a total of 11 companies, and used a purposive sampling technique. The results of this study state that there is a partially significant effect between Revenue, Tax To Book Ratio, and Taxable Income on Company Performance, and there is a partially insignificant effect between Deferred Tax and Current Tax on Company Performance. Then, the simultaneous results of Income, Tax to Book Ratio, Taxable Income, Deffered Tax and Current Tax have a significant effect on the Company's Financial Performance.